Investigation of micronuclei in rats’ bone marrow under joint exposure of endogenic nitrosamines and electromagnetic field of industrial frequency (50 Hz) (Environment & Health, 2017)
Objective: We studied a genotoxicity of joint exposure of endogenic nitrosamines and electromagnetic field of industrial frequency.Materials and methods: The experiment was performed on 160 white outbred female rats of 6-8 weeks age with a weight of 140-154 g, divided into 4 groups: intact control; introduction of nitrosamines’ synthesis precursors (NAP) – sodium nitrite, 100 mg/kg; tetracycline, 20 mg/kg; irradiation by electromagnetic field of industrial frequency (EMF IF), 50 Hz, 90 µT; joint exposure of NAP and EMF IF. NAPs were introduced once a day, 5 days per week during 90 days. Irradiation by EMF was carried out at the same terms for 7 hours daily. Endogenic synthesis was controlled by the chromatographic determination of nitrosamines’ content in liver and kidneys of the rats. Genotoxicity was determined by micronucleus test in bone marrow polychromatic erythrocytes (PCE) of femoral bones within 24 hours after last introduction.Calculation of MN PCE was carried out in 3 smears from each animal. We determined individual and group indices of micronuclei frequency (%) on 2000 PCE. Obtained data were analyzed statistically with the help of Student t-test.Results: The reliable increase of micronuclei frequency (0.13 %, р < 0.05) was observed under isolated administration of NAP in comparison with intact control (0.08 %). A tendency to the increase of MN frequency (0.12 %, р > 0.05) was observed in the rats irradiated by EMF. At the same time the joint effect of the factors caused the reliable strengthening of the effect (0.18%, р
Keywords: nitrosamines; electromagnetic fields of industrial frequency; joint effect; rats; genotoxicity; micronuclei; bone narrow